International trade policy : from tariffs to the new protectionism - Greenaway, David (London Macmillan, 1985)
This text is written principally for the consumption of undergraduates following courses in international economics and international trade.
includes index and bibliographic reference, index
ijb, 15/01/2019
Loans
Keywords: Foreign trade regulations; Tariff; Trade policy - international